2020
DOI: 10.1113/ep088458
|View full text |Cite
|
Sign up to set email alerts
|

Individual risk factors associated with exertional heat illness: A systematic review

Abstract: Despite the widespread knowledge of exertional heat illness (EHI) and clear guidance for its prevention, the incidence of EHI remains high. We carried out a systematic review of available literature evaluating the scientific evidence underpinning the risk factors associated with EHI. Medline, PsycINFO, SportDiscus and Embase were searched from inception to January 2019 with no date limitation, with supplementary searches also being performed. Search terms included permutations of risk and heat illness, with on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 53 publications
6
37
1
Order By: Relevance
“…Although the evidence was either limited or conflicting, other intrinsic risk factors that were found to have some form of association with EHI were age, marital status, acclimatisation, pre-existing illness, race and genetics. These intrinsic factors are in consonance with a recently published review that identified a variety of intrinsic/individual factors associated with EHI in the general population [ 65 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although the evidence was either limited or conflicting, other intrinsic risk factors that were found to have some form of association with EHI were age, marital status, acclimatisation, pre-existing illness, race and genetics. These intrinsic factors are in consonance with a recently published review that identified a variety of intrinsic/individual factors associated with EHI in the general population [ 65 ].…”
Section: Discussionsupporting
confidence: 87%
“…However, in this review, heat acclimatisation was not significantly associated with EHI. It is important to apply caution when interpreting the association between physical fitness and EHI among military personnel, given that these findings were as a result of failing occupational fitness tests among recruits or new enlistees [ 65 ]. Furthermore, the choice of tests used to assess fitness may not provide true reflections of the aerobic fitness levels of the military personnel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pathology of some of the conditions that constitute HI are better understood than NFCI, they can still vary in terms of the organs affected in different individuals and the sensitivity of different individuals to the same conditions and responses. As with NFCI, lists of factors that predispose to HI have been produced (Westwood et al., 2020), but none of these applies in all conditions.…”
Section: Figurementioning
confidence: 99%
“…From the pathophysiological/clinical perspective, Trotter and colleagues report that high‐intensity interval exercise reduces tolerance to a simulated haemorrhagic challenge in heat‐stressed individuals (Trotter et al., 2021). There is a systematic review of individual risk factors associated with exertional heat illness (Westwood et al., 2021). Two papers examine the medical emergency of heat stroke: one describes the acute phase response to exertional heat stroke (Iwaniec et al., 2021), the other the impact of prior viral illness on heat stroke severity (Dineen, Ward, & Leon, 2021).…”
mentioning
confidence: 99%